Potensi Indonesia-Malaysia-Singapura (IMS-GT) Sebagai Stumblinh Block terhadap Masyarakat Ekonomi ASEAN - Novita Putri Rudiany; Puti Tantia Anugrah (Andalas Institute of International Studies, 2020)
This article is about cooperation in the Southeast Asia, namely Indonesia-Malaysia-Singapore Growth Triangle, which can be the stumbling block towards the ASEAN Economic Community. Indonesia-Malaysia-Singapore Growth Triangle (IMS-GT) is a growth triangle cooperation between Indonesia, Malaysia, and Singapore. This cooperation has been going on for more than 20 years and now it works in line with the existence ASEAN Economic Community (AEC). AEC is a form of ASEAN cooperation that wants to realize economic integration in the Southeast Asia. AEC also aims to create an area that has high investment flow with programs to be taken. However, with the existence of IMS-GT, the achievement of AEC can be hampered. Thus, this study will analyze how the IMS-GT sub-regional cooperation can impact the process of AEC. The method used is a qualitative method. The results show that IMS-GT has the potential to become a stumbling block for AEC. This article will only focus on the forms of collaboration IMS-GT, so that other forms of cooperation will not be discussed.Keywords: IMS-GT, sub-regional cooperation, AEC, stumbling block